Enhanced uptake and siRNA-mediated knockdown of a biologically relevant gene using cyclodextrin polyrotaxane1. Issue 13 (7th April 2015) - Dandekar, P.; Jain, R.; Keil, M.; Loretz, B.; Koch, M.; Wenz, G.; Lehr, C.-M.
<x xml:space="preserve">Abstract</x> Cellular investigations confirm the ability of cyclodextrin polyrotaxane nanoplexes to deliver siRNA for down-regulating genes relevant to the pathogenesis of tuberculosis.